Foodscapes, foodfields, and identities in Yucatán - Ayora Díaz, Steffan Igor (Latin America studies, 2012)
The state of Yucatán has its own distinct culinary tradition, and local people are constantly thinking and talking about food. They use it as a vehicle for social relations but also to distinguish themselves from "Mexicans." This book examines the politics surrounding regional cuisine, as the author argues that Yucatecan gastronomy has been created and promoted in an effort to affirm the identity of a regional people and to oppose the hegemonic force of central Mexican cultural icons and forms. In particular, Yucatecan gastronomy counters the homogenizing drive of a national cuisine based on d.